MODELS FOR PHYSICAL AND NUMERICAL SLOPE FAILURE OF LOOSE SAND UNDER DYNAMIC LOADING - ZULFAHMI ZULFAHMI (Indonesian Mining Journal, 2012)
Excessive vibration that causes damage to model the medium such as mine slope can physically and numeri- cally be modelled. The slope of this study simply represents the actual view of the slopes that has a smaller size than the actual one, while the numerical model is relates to a mathematical form of slope condition that based on physical and mechanical data of the medium. The slope failure has experimentally been built several variations. Effect of vibration is echieved by connecting the models into the vibration instrument with bearing that can horizontally move free in line within the determined track. The instrument is attached to a spring that can pull the model to side out. The spring is placed in an iron frame. Proviously, the slope has been formed in critical condition one (angle of 30°). Physical model and laboratory test results were used as an input for numerical modelling of the slope failure. Based on the numerical analysis, the SRF was 0.47 for D equal to 2 cm g around 0.0025. If the g’s were around 0.0057 and 0.0088, the obtained SRF for both g’s were 0.44 and0.41 respectively. While the D of 4 cm and g of 0.0024 came the SRF of 0.54, the g of 0.0064 derived the SRF of 0.48, and the g of 0.0106 obtained the SRF of 0.44. For D equal to 2 cm and g 0.0024, 0.0106; the obtained SRF was 0.54, 0.48 and 0.44 respectively. Increasing the D to 6 cm within variation of g from 0.0025, 0.0062 and 0.0106, the SRF was 0.51, 0.48 and 0.44 respectively. It is assumed that there is a correlation between the thickness of quartz sand layer and the decrease of SRF value. The correlation also occurs between the increase in vibration (g value) and the SRF.